Palm oil based wax as an alternative resist agent for batik canting / Hamdan Haji Lias - Lias (Haji), Hamdan (2007)
Paraffin wax. has being used as a resist agent by the.batik manufacturers in Malaysia since 1930. The wax together with chemicals rosin acted as a resist agent in making the batik,canting, batik cop and batik printing. Due to inadequate supplies of paraffin wax which happened in 1965, this research focused to identify an alternative to paraffin wax in order to minimize the dependency of batik canting industry towards paraffin wax. An alternative to paraffin identified in this study is Palm oil based wax which the samples of it were taken from the Malaysian Palm Oil Boar (MPOB). There were ele,venexperiments conducted to determine that the Palm oil based wax is' capable to substitute paraffin. as a resist agent. for batik canting. The capabilities of Palm oil based wax were tested to see the effectiveness of the·Palm oil based wax as a resist agent· on three different types of fabrics namely satin' silk, rayon and .cotton with three different sizes of canting tools. Each fabric required different proportion of Palm oil based wax and rosin to act as an effective resist agent. The effective resist agent basically is able to block'out the dyes from dispersing from the outline that drawn by the batik wax.